Jakarta Islamic Index Stock Volatility and Forecasting Using Realized GARCH Model - Muhammad Faturrahman Aria Bisma; Faizul Mubarok (Majalah Ilmiah Bijak, 2021)
Along with the large number of investors transacting on Islamic stocks, stock prices' movement becomes more volatile. The purpose of this research is to examine the behavior of volatility patterns in shares incorporated in the Jakarta Islamic Index using the Generalized Autoregressive Conditional Heteroskedasticity (GARCH) model. This study uses daily data from six stocks in the Jakarta Islamic Index during the period of January 1, 2009, to December 31, 2019. Data volatility is seen using the GARCH model. Estimation results for daily data show that the volatility of ASII, SMGR, TLKM, UNTR, and UNVR shares is influenced by the previous day's error and return volatility. This is indicated by the GARCH effect on each regression result. The study results are beneficial for an investor, and invest with a low level of risk can choose TLKM shares. Nevertheless, if going to get a high level of return can invest in UNTR shares. For securities, analysis can use the GARCH model tested to predict volatility in the Jakarta Islamic Index.